Hikmah Behind The Academic in The Islamic Economy - Nur Hadi (Ijtimā`iyya: Journal of Muslim Society Research, 2019)
The relationship between one human being and another in fulfilling needs (min min al-Nas), there must be a rule that explains both rights and obligations based on agreement (contract). Humans are never separated from the contract (contract / agreement) in their lives. A contract is a bond of consent (statement of acceptance of a bond) and Kabul (statement of acceptance of a bond) in accordance with the will of the Shari'a which affects the object of engagement (contract). Because of the importance of the contract in human life, of course every thing has wisdom, then what is the nature of wisdom and how are the wisdom of the contract in Islamic economics. The essence of wisdom is an expression that refers to a solid knowledge, which includes (can lead to) makrÃ®fah (recognition) to Allah, which comes from the pure inner eye, and the ability of the knowledge to learn and understand the nature of things in their objective state the realm of reality is limited to the supreme ability of humans in finding and discovering the secrets of the shari'a religion (law) and the purpose of Islamic law. While the wisdom of the contracts in Islamic economics are: 1). Moral and material accountability of both parties emerged; 2). The emergence of a sense of tranquility and satisfaction from both parties; 3). Avoidance of disputes from both parties; 4). Avoid legitimate ownership of property; 5). Ownership status of property becomes clear; 6). There is a strong bond between two or more people in transacting or having something; 7) It cannot be arbitrary in canceling an agreement, because it has been set in shar'i; 8). A contract is a "legal umbrella" in possession of something, so that the other party cannot sue or have it. In simple terms the wisdom of the Covenant is an attempt to uncover the truth, practice the truth and fight lust from all forms of evil and realize benefit and reject damage in the muamalah contract of Islamic economics.